Actinic Flux measurements during OASIS Barrow field intensive Spring 2009 (Arctic Data Center, 2016)
A measurement intensive campaign was carried out in Barrow, Alaska, in spring 2009 as part of the Ocean Atmosphere Sea Ice Snowpack (OASIS) program. The central focus of this campaign was the role of halogen chemistry in the Arctic. This dataset contains atmospheric photolysis frequencies at the surface. These data were calculated from the actinic flux measured by the CCD Actinic Flux Spectroradiometers (CAFS). Data are in tab-separated data format (TAB) and are located within one ZIP file.